2015
DOI: 10.1177/1947603514566298
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Allograft Transplantation for Knee Lesions after Failure of Cartilage Repair Surgery

Abstract: Objective:The objective of this study was to assess the outcome of osteochondral allograft (OCA) transplantation as a salvage procedure after various cartilage repair surgeries.Design:One hundred sixty-four knees in 163 patients (mean age = 32.6 years; range = 11-59 years; 55% males) were treated with OCA transplantation after subchondral marrow stimulation (SMS), osteochondral autograft transplantation (OAT), and autologous chondrocyte implantation (ACI). The majority of previous procedures were isolated SMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 40 publications
0
70
1
2
Order By: Relevance
“…7,35,78 Even though the sandwich technique has been described in the treatment of bone lesions concomitantly with ACI, there was no agreement on its utilization, and OCA was preferred for cases that include intralesional osteophytes, revision including prior failed microfracture, prior fracture malunion, significant subchondral stress reactions also known as "bone edema," significant subchondral cyst formation, and bone loss due to fractures or osteochondritis dissecans fragment excision. 21,31,36,38,60,62,75,79 In the patellofemoral joint, morphology matching makes OCA technically more demanding than ACI. This is because of the complex topography, with highly variable shapes of the patella and trochlea.…”
Section: Indicationsmentioning
confidence: 99%
“…7,35,78 Even though the sandwich technique has been described in the treatment of bone lesions concomitantly with ACI, there was no agreement on its utilization, and OCA was preferred for cases that include intralesional osteophytes, revision including prior failed microfracture, prior fracture malunion, significant subchondral stress reactions also known as "bone edema," significant subchondral cyst formation, and bone loss due to fractures or osteochondritis dissecans fragment excision. 21,31,36,38,60,62,75,79 In the patellofemoral joint, morphology matching makes OCA technically more demanding than ACI. This is because of the complex topography, with highly variable shapes of the patella and trochlea.…”
Section: Indicationsmentioning
confidence: 99%
“…8 In a similar study, Gracitelli et al demonstrated 82% osteochondral allograft survival at 5 years and 74.9% survival at 15 years in patients with prior failed cartilage repair surgeries. 9 These studies, combined with our own experiences, demonstrate that large OATs for tibial surface chondral defects are a viable treatment option in patients with severe, post-traumatic chondral defects.…”
Section: Discussionmentioning
confidence: 70%
“…As described by Berta et al (2015), this technique offers effective management of small and medium-sized focal defects although it does not result in good hyaline cartilage. Allotransplantation is particularly considered for settings that require whole structures such as menisci, large number of cells and/or when other techniques of cartilage repair have failed Gracitelli et al, 2015). Despite the clinical benefit attained with meniscus allotransplantation and osteochondral allograft transplantation Gracitelli et al, 2015), some concerns have been raised about the potential detrimental effects of the elicited immune response.…”
Section: R Sommaggio Et Al Barriers To Chondrocyte Xenotransplantationmentioning
confidence: 99%
“…Allotransplantation is particularly considered for settings that require whole structures such as menisci, large number of cells and/or when other techniques of cartilage repair have failed Gracitelli et al, 2015). Despite the clinical benefit attained with meniscus allotransplantation and osteochondral allograft transplantation Gracitelli et al, 2015), some concerns have been raised about the potential detrimental effects of the elicited immune response. Evidence is accumulating of the immune-privileged properties of cartilage, but isolated chondrocytes and especially the bony portion of the osteochondral grafts are more immunogenic (Smith et al, 2015).…”
Section: R Sommaggio Et Al Barriers To Chondrocyte Xenotransplantationmentioning
confidence: 99%